Mc cune albright syndrome - Clinicoradiological diagnosis of a rare case - Anka Sharma; Anirudh Upmanyu; Vikrant O Kasat; Amit R Parate (Wolters Kluwer Medknow Publications, 2021)
Mc Cune Albright Syndrome (MAS) is a rare, sporadic disorder characterized by a triad of symptoms: fibrous dysplasia, cafe-au-lait spots, and endocrinopathy. It is thought to be caused by the mutation of the GNAS1 gene and is predominantly a disease of females. We hereby report a case of a 40-year-old man who presented with suppuration and mobility of teeth in the maxillary left posterior region. The patient also had a history of recurrent fractures of limbs since childhood. Clinical examination revealed asymmetry of the face, brownish-tan macules on the nape of the neck, back, and bilateral buccal mucosa as well as lower labial mucosa. The radiological investigation confirmed the presence of polyostotic fibro-osseous lesion while the biochemical investigations revealed endocrinopathy (hyperparathyroidism). This case report emphasizes the role of an oral physician in arriving at the diagnosis of a complex disorder like MAS.